Effectiveness of an 810-nm Diode Laser in Addition to Non-surgical Periodontal Therapy in Patients With Chronic Periodontitis: A Randomized SingleBlind Clinical Trial: Effectiveness of Diode Laser in Addition to SRP in Chronic Periodontitis - Mokhtari, Majid Reza; Ahrari, Farzaneh; Dokouhaki, Shokoufeh; Fallahrastegar, Amir; Ghasemzadeh, Alireza (Journal of Lasers in Medical Sciences, 2021)
Introduction: This study evaluated the effectiveness of an 810-nm diode laser as an adjunct to scaling and root planning (SRP) in improving periodontal parameters in patients with chronic periodontitis. Methods: This randomized clinical trial consisted of 36 patients (16 females and 20 males) with chronic periodontitis and pocket depths of 4-6 mm. The quadrants were randomly divided into two sides; one side of each patient was selected as the laser group (SRP + laser) and the other side served as the control group (SRP alone). An 810-nm diode laser was applied in the laser side to remove the outer gingival epithelium (1.5 W, CW) as well as the inner epithelium of the periodontal pockets (1 W, CW). The clinical parameters including bleeding on probing (BOP), probing depth (PD), plaque index (PI), and clinical attachment level (CAL) were measured at baseline and 6 and 18 weeks after therapy. Results: In both groups, there was a significant improvement in BOP, PD, PI and CAL over the course of the experiment (P<0.001). Significantly lower BOP was found in the SRP + laser group than the SRP alone group after 6 and 18 weeks of intervention (P<0.05). The difference in other parameters was not significant between the two groups, neither at 6 nor at 18 weeks after the treatment (P>0.05). Conclusion: Within the limitations of this study, the association of the diode laser with standard nonsurgical periodontal therapy (SRP) provided minimal additional benefits for patients with moderate chronic periodontitis Doi:10.34172/jlms.2021.37